Barriers to Competition in Croatia : The Role of Government Regulation - De Rosa, Donato (2012)
This paper examines product market policies in Croatia by benchmarking them to OECD countries and highlighting how policies that are more conducive to competition would stimulate a more efficient allocation of resources and, in consequence, facilitate convergence to higher income levels. OECD indicators of overall regulation in product markets indicate that Croatias policies in 2007 were generally more restrictive of competition than were the policies in OECD countries. This is especially true for policies concerned with the degree of state control of the economy and with barriers to entrepreneurship. Regulatory obstacles to trade and foreign direct investment, by contrast, are in line with those of pre-accession European Union countries (Czech Republic, Hungary, Slovak Republic, and Poland in 2003, as well as Bulgaria and Romania in 2006), albeit well above the OECD average. Regulation of post, electricity, gas, telecoms, air, rail, and road transport, as estimated by the OECD energy transport and communication sectors indicator, is also less liberal than in the OECD, highlighting the positive knock-on effects for the rest of the economy that could derive from further liberalization of network industries.